Case Study : Zaine Textile / Ahmad Azri Zakaria - Zakaria, Ahmad Azri (2021)
I have chosen Zaine Textile Company for my case study. Zaine Textile is a company that provides various types of quality and the latest batik fabrics available on stores! The fabrics sold by the company are high demand in fashion. The boutique of Zaine Textile is owned by Nik Yuzaine bin Nik Yusoff, who is an alumni student of UNITAR International University. This owner has taught me the ins and outs about businesses in the real world. The business operation is open every day from 10:00 a.m. to 6:00 p.m. The business also advertises their product through Facebook to get more recognition by consumers. The business is evaluated by its performance in business by SWOT analysis which imply strength, weakness, opportunity, and threat. Through this, I can figure out the problem and find solution based on the analysis made for the company. From my own observation, I can identify the characteristic the entrepreneur and its entrepreneurial competencies.